Effects of Boxing Matches on Metabolic, Hormonal, and Inflammatory Parameters in Male Elite Boxers - Kilic, Yakup; Cetin, Hasan N.; Sumlu, Esra; Pektas, Mehmet B.; Koca, Halit B.; Akar, Fatma (Mdpi, 2019)
Background and objectives: Boxing is a popular combat sport that requires high intensity and cooperation. However, there are limited data about the influence of boxing matches on blood parameters. The purpose of the present study was to investigate the match-induced changes in the metabolic, hormonal, and inflammatory status in male elite boxers. Materials and methods: High-level 20 male boxers with more than 5 years experience in boxing voluntarily participated in this study. Venous blood samples of the boxers, before and after combat, were taken for determination of the plasma parameters. Results: Our results indicated that a 9-min boxing match caused significant increases in plasma energy fuels (glucose and lactate), metabolic hormones (insulin, adrenocorticotropic hormone (ACTH), cortisol, and growth hormone), inflammatory markers (interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-alpha)), muscle damage indicators (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)), and oxidative stress marker (SOD). A decrease in total oxidant status (TOS) was also considered. However, there were no significant alterations in the plasma levels of androgenic hormone (free and total testosterone), anabolic hormone (IGF-1), lipids (total cholesterol, triglyceride, high-density lipoprotein (HDL), and low-density lipoprotein (LDL)), kidney function markers (creatinine and urea), and minerals (iron (Fe) and magnesium (Mg)). Conclusion: Elevations in the level of energy fuels and metabolic hormones of the boxers could be taken as a reflection of high-energy turnover during combat performance. The increases in inflammatory and tissue damage indicators may possibly be an indication of traumatic injury. Understanding the biochemical changes that occur during boxing match could be valuable to optimize the performance improvement of the athletes.
Keywords: exercise; boxing match; metabolic and hormonal parameters; inflammatory markers; muscle damage indicators